The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.11648/j.nano.20200803.11
|View full text |Cite
|
Sign up to set email alerts
|

Surface and Quantum Effects in Nanosized Semiconductor

Abstract: Novel properties of nano-scale semiconductors based on the surface and quantum effects have been studied and applications identified. Spherical potential well model is used to study quantum effect whereas basic geometrical models are used for the surface effect. We have shown such effects to be the fundamental factors responsible for the novel nanosized semiconductor characteristics different from the bulk of same material. It is found that the surface area to volume ratio follows inverse power law. Thus at na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…The incorporation of QDs that simultaneously offer an improved optical absorption, photo-excited carrier collection and phonon bottleneck effects are presently being explored. QDs are semiconductors in nanometer dimensions providing strong quantum confinements on the carriers in 3D leading to discrete and size dependent energy spectrum in sharp contrast to the bulk matter whose electronic states are distributed in continuous bands as depicted in Figure 4, thus making QDs typical example of live quantum mechanical phenomenon [24]. The discrete energy level spectrum in QDs is a replica of atomic energy spectra which confers on them the moniker "artificial atoms" [25].…”
Section: Fig 1 Basic Operation Of Solar Cellmentioning
confidence: 99%
“…The incorporation of QDs that simultaneously offer an improved optical absorption, photo-excited carrier collection and phonon bottleneck effects are presently being explored. QDs are semiconductors in nanometer dimensions providing strong quantum confinements on the carriers in 3D leading to discrete and size dependent energy spectrum in sharp contrast to the bulk matter whose electronic states are distributed in continuous bands as depicted in Figure 4, thus making QDs typical example of live quantum mechanical phenomenon [24]. The discrete energy level spectrum in QDs is a replica of atomic energy spectra which confers on them the moniker "artificial atoms" [25].…”
Section: Fig 1 Basic Operation Of Solar Cellmentioning
confidence: 99%
“…The availability of copper has made it a better choice to work with because it shares properties similar to those of other expensive noble metals, including silver and gold. The choice of copper in the present research is attributed to the factors mentioned above; copper nanoparticles are reported to have antimicrobial activity against several species of bacteria and fungi [8,[10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%